THE RELATIONSHIP BETWEEN PATIENTS' KNOWLEDGE ABOUT HYPERTENSION AND COMPLIANCE ATTITUDES IN FOLLOWING A HYPERTENSION DIET - Sry Rizki (Journal of Innovative and Creativity, 2026)
Background: Hypertension is known as a silent disease because many people are unaware they have it until they have their blood pressure checked. Diet plays an important role in managing hypertension. A healthy lifestyle and proper nutrition among individuals with high blood pressure can help control blood pressure, and when combined with reduced salt intake, it can lead to a decrease in blood pressure. Objective: To determine the relationship between patients’ knowledge about hypertension and their attitudes toward compliance in following a hypertension diet in the working area of UPTD Puskesmas Meukek, South Aceh Regency. Method: This study used a descriptive correlational non-experimental design with a cross-sectional approach. The sample consisted of 89 patients receiving treatment at UPTD Puskesmas Meukek. Results: The study showed a p-value of 0.014 (< 0.05) for the relationship between knowledge level and dietary compliance, and a p-value of 0.000 (< 0.05) for the relationship between attitude and dietary compliance. Conclusion: There is a significant relationship between knowledge and attitude levels and compliance in following a hypertension diet in the working area of UPTD Puskesmas Meukek, South Aceh Regency. Recommendation: The results of this study may serve as a reference to help improve attitudes and compliance in following a hypertension diet.